A comparative study of the efficacy of instrument-assisted soft tissue mobilization and massage techniques in patients with patellofemoral joint pain - Liu, Yang; Wang, Yidan (Frontiers in Medicine, 2023)
Purpose The aim of this study was to compare the clinical efficacy of instrument-assisted soft tissue mobilization (IASTM) and manipulative therapy Tui-na techniques in the treatment of patients with patellofemoral joint pain syndrome, and to evaluate their impact on pain relief, functional improvement, and joint range of motion. Methods In this study, 25 patients with patellofemoral pain syndrome were enrolled, comprising of an intervention group of 13 patients who received IASTM treatment and a control group of 12 patients who received Tui-na manipulation therapy. The treatment cycle lasted for 4 weeks, featuring two interventions per week. Before treatment, the visual analog pain scale (VAS) of the knee, Lysholm score of the knee, modified Thomas test (MTT), and maximum isometric strength of the extensor muscles of the lower limbs were measured and recorded for both groups. After the first and last treatments, the aforementioned indexes were reassessed, and the maximum isometric muscle strength of the lower extremity extensors was measured only after 4 weeks of treatment had been completed. Results There was no significant difference in the basic information of the two intervention groups (p > 0. 05). After the first treatment and 4 weeks of treatment, the Lysholm score in both groups significantly improved (p < 0. 05), indicating that both interventions can improve the function of patients’ lower limbs. However, the Lysholm score in the IASTM group significantly increased compared with that of the massage group after 4 weeks of treatment, indicating that its improvement in functional performance is superior. Both groups showed significant improvement in knee joint pain after the first treatment and 4 weeks of treatment (p < 0. 05), with the IASTM group having a lower VAS score and better pain improvement after 4 weeks of treatment. The strength of the two intervention groups significantly increased after the maximum isometric muscle strength test of the lower limb extensor muscles before and after 4 weeks of treatment (p < 0. 05). After the MTT test, the extension angle, deviation angle, and hip abduction angle of the tested legs in the two intervention groups were significantly reduced (p < 0. 001), indicating an improvement in lower limb joint mobility. Conclusion Instrument-assisted soft tissue mobilization treatment and Tui-na manipulation therapy significantly reduced pain, improved knee flexibility, and increased range of motion of the lower extremity in patients with PFPS. However, IASTM treatment significantly improved pain and function and sustained pain in the short to medium-term post-trial period. Clinical trial registration www.isrctn.com, ISRCTN88098928